Perceptions and Adoption Trends of Artificial Intelligence in Portfolio Construction and Management in the Financial Services Industry of South Africa - Agjee, Zeyn (University of the Witwatersrand, Johannesburg, 2024)
The adoption of Artificial intelligence (AI) in portfolio construction promises to revolutionise financial services, offering opportunities to enhance efficiency, foster innovation, and drive disruptive change. This qualitative study investigates the perspectives and adoption trends of AI-driven portfolio construction methods among South African financial services organisations. The research uncovers attitudes, challenges, and aspirations surrounding AI adoption through in-depth interviews with nine industry professionals. The study finds that while there is widespread enthusiasm within the industry for AI adoption in portfolio construction and the industry, professionals express reservations about trust, lack of understanding, data challenges, costs and AI's efficacy in navigating the complexities of the South African market. The study highlights complexities in AI adoption, including transparency, regulatory compliance, accountability, data considerations, overfitting issues, human-machine interactions, lack of agility in companies and potential job displacement concerns. Despite the increasing acceptance of AI in investment management, significant obstacles persist, necessitating concerted efforts to address problems and cultivate trust and openness within the industry. The paper presents valuable insights into the patterns of AI adoption in South Africa, offering practical recommendations for industry practitioners, policymakers, and researchers. It emphasises the importance of trust-building strategies among industry practitioners, highlighting the need for transparent communication and ethical considerations throughout AI adoption. Additionally, the paper underscores the role of policymakers in developing regulatory frameworks that promote responsible AI integration, advocating for guidelines that uphold ethical principles and protect consumer rights Further, there is a call for continued support for research and development efforts tailored to the South African market, aiming to address specific challenges and foster innovation in AI technologies. Overall, the findings emphasise the necessity of collaboration between stakeholders to ensure the ethical and widespread practical adoption of AI in South Africa's financial sector
A research report submitted for the partial requirements for the degree of MBA in the graduate school of business administration (WBS) faculty of commerce, law and management university of Witwatersrand, Johannesburg 2024
Keywords: Artificial Intelligence (AI); Portfolio Construction; AI Adoption; Asset Allocation; Perceptions of AI; UCTD; SDG-9: Industry, innovation and infrastructure